PENGARUH PROFESIONALISME GURU DAN PERAN ORANG TUA TERHADAP PRESTASI BELAJAR AL-QUR’AN HADITS SISWA KELAS X DI MAN 7 JOMBANG TAHUN PELAJARAN 2015/2016 - Nining Aslihah; Dian Triana; Atim S (Arsy : Jurnal Studi Islam, 2018)
Professionalism correlation Learns And oldster Role With Al Qur's Learned Achievement ’ an Hadits Student brazes x MAN 7 Jombang School Years 2015 / 2016. Have our a lot of meets research that works through about studying. But then, research that work through Professionalism Influence Learns and oldster Role to Al Qur's learned achievement ’ an Hadits student brazes x at MAN 7 Jombang School Years 2015 / 2016 is still so minim.With marks sense this research, therefore expected Professionalism Learns, Oldster and party role that have influences to Al Qur's learned achievements ’ an Hadits student brazes x MAN 7 Jombang, that realises just how the importance for student studying achievement Al Qur ’ an Hadits brazes x MAN 7 Jombang School Years 2015 / 2016 one is expected to sail through succeeding ladders. Therefore Profresionalisme Learns at Madrasah shall be applied, so also highly expected oldster Role that one becomes student aspiration can be reached.Data about Teacher Professionalism And oldster Role is gotten of 47 students as respondent as through questionnaire and Al Qur's studying achievement ’ an Hadits student brazes x MAN 7 Jombang School Years 2015 / 2016 taken from by raport's points of 47 students. Meanwhile data analysis tech that is used is analisis regression.Result observationaling to point out partially, there is influence which positive and signifikan among teacher professionalism and oldster role to Al Qur's learned achievement ’ an Hadits student brazes x MAN 7 Jombang School Years 2015 / 2016 one is proven through quizs t therefore acknowledged that all point t computing > t table , it means that variable second free partially influential positive and signifikan to bonded variable, X 1: t = 7,074 sig = 0,00( sig / p< 0,01) and x 2: t = 2,563 sig =0,014 (sig / p< 0,05)simultan's ala, there is influence which positive and signifikan among teacher professionalism and oldster role to Al Qur's learned achievement ’ an Hadits student brazes x MAN 7 Jombang School Years 2015 / 2016 one proved by both of variable frees ascendants to bonded variables (learned achievement) one that is proven quiz thru f one points out that f = 35,937 sig = 0,00( p / sig< 0,01) and its influence as big as 62%.